A midstream urine collector is not a good alternative to a sterile collection method during the diagnosis of urinary tract infection. (4th May 2015) - Verliat‐Guinaud, J; Blanc, P; Garnier, F; Gajdos, V; Guigonis, V
Abstract Aim Guidelines recommend collecting urine with suprapubic aspiration or urethral catheterisation in infants with a suspected urinary tract infection (UTI), but the invasiveness of these methods continues to drive research on new urine collection devices. We studied children with a suspected UTI, who had not been toilet trained, to compare a new midstream urine collector and catheterisation. Method During this prospective controlled diagnosis study of 94 children, urine collection was performed using the midstream collector and then controlled via catheterisation when the urine dipstick was positive. Results When end stream samples collected by the midstream collector were compared to catheter samples, the results were inconsistent in 23.4% of cases, similar to the inconsistent results between first stream samples discarded by the device and the catheter samples (21.3%). Interestingly, the overall rate of sample contamination in the bag of the midstream collector was lower than that reported in previously published studies and there were no false positive bag results. Conclusion The midstream collector did not appear to provide additional benefits to classic collection bags. A sterile collection method, such as suprapubic aspiration, catheterisation or clean catch, is still mandatory for diagnosing urinary tract infections in children who are not toilet trained.